QR Code Pop-up Book Based on Ethnomathematics to Improve Problem Solving Skills - Dewi, Ni Kadek Dita Cahyani; Widiana, I Wayan; Jayanta, I Nyoman Laba (Universitas Pendidikan Ganesha, 2024)
Lack of optimization of the application of learning media and the application of methods used in the implementation of the elementary school mathematics learning process is the background of this study. This study has four objectives, namely: (1) analyzing the validity of learning media, (2) analyzing the practicality of learning media, (3) analyzing the effectiveness of ethnomathematics-based QR code pop-up book learning media to improve students' problem-solving abilities in mixed calculation operation material grade III elementary schools. The research model used in this study is the ADDIE model which consists of five stages, namely analyze, design, development, implementation, and evaluation. The subjects in this study were 4 experts, and 33 elementary school students. This research trial motorcycle taxi is the problem-solving ability of students in the operation material to calculate the number of cacah class III elementary schools. The data collection methods used are questionnaires and tests. The instrument applied to collect data is a questionnaire in the form of a closed type of questionnaire using a rating scale and an essay test. The results showed that (1) the learning media that had been produced obtained a very good expert validity index, (2) the level of achievement of practicality of learning media in terms of student responses obtained very good qualifications, (3) the implementation of research on correlated t-tests obtained significant results so that ethnomathematics-based QR code pop-up book learning media was effective for improving problem solving skills in class mixed calculation operation material III elementary school.